PROFIL KEMAMPUAN GURU-GURU IPA SMP se-BANDAR LAMPUNG DALAM MELAKUKAN KEGIATAN PRAKTIKUM - Dina Maulina (Universitas Lampung, 2014)
Practicum is one vehicle for learning science in the implementation of the curriculum in 2013. Teacher as a model to be able to carry out practical activities. The purpose of this study was to determine the ability of junior high school science teachers in Bandar Lampung to conduct laboratory activities. The research sample were 69 junior high school science teacher in Bandar Lampung. The analysis used is descriptive analysis. The results showed that in general the average 51.7% of teachers have not been able correspondent practicum activities correctly, with details of 65% has not been able to test the activities of food substances; 29% have not been able to perform photosynthesis activity; 62% have not been able to carry out practical activities respiration test. Thus, it can be conluded that the ability of junior high school science teachers in Bandar Lampung on carrying out practical activities are still low catagorize.Kegiatan praktikum merupakan salah satu wahana pembelajaran IPA dalam implementasi kurikulum 2013. Guru sebagai model harus mampu dalam melakukan kegiatan praktikum. Tujuan dari penelitian ini adalah untuk mengetahui kemampuan guru-guru IPA SMP se-Bandar Lampung dalam melakukan kegiatan praktikum. Sampel penelitian ini adalah 69 orang guru IPA SMP se-Bandar Lampung. Analisa yang digunakan menggunakan analisis deskriptif. Hasil Penelitian menunjukan bahwa secara umum rata-rata 51,7% koresponden guru belum mampu melakukan kegiatan praktikum dengan benar. Dengan rincian 65% belum mampu melakukan kegiatan uji kandungan zat makanan; 29% belum mampu melakukan kegiatan fotosintesis; 62% belum mampu melaksanakan kegiatan praktikum uji respirasi. Dengan demikian dapat disimpulkan bahwa kemampuan guru-guru IPA SMP se-Bandar Lampung dalam melaksanakan kegiatan praktikum masih berkatagori rendah.Kata kunci: guru IPA, praktikum, uji fotosintesis, uji kandungan zat makanan, uji respirasi